Developing an approach to report scope 3 emissions in South African mines - Mashila, Tlangelani (Stellenbosch : Stellenbosch University, 2025)
Mashila, T. 2025. Developing an approach to report Scope 3 emissions in South African mines. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/70cda122-378a-4cad-9ffc-1097847894ed